Cassius Dio und die Römische Republik : Untersuchungen zum Bild des römischen Gemeinwesens in den Büchern 3-35 der Rhomaika - Simons, Benedikt (Beiträge zur Altertumskunde, 2009)
Previously Cassius Dio℗þs Romaika (c. AD 160 - c. AD 230) has generally served as a quarry for the reconstruction of lost sources and the historical narrative. On the other hand, the view of the Roman Republic held by this member of the imperial elite has hardly been considered. This work combines two separate strands of research, in that it examines the criteria according to which he employed his sources: he adhered to an ideal of a harmonious society which was particularly influenced by the Stoic Poseidonios (c. 135 - c. 51 BC), according to which everybody served for the good of all.